Ghost network analyzer. (23rd January 2020) - Zhang, Xiao; Yin, He; Li, Rui; Hong, Jiaying; Li, Qin; Xue, Ping
Abstract: Ghost imaging obtains an image of an amplitude/phase object by spatial correlation between two separated light beams. In ghost imaging, two detectors are used in a counter-intuitive way. One is a multi-pixel detector that does not view the object in reference arm, and the other one is a single-pixel detector that does view the object but only record the total light power in object arm. Neither detector could recovery the object independently, but spatial correlation from two detectors allows the reconstruction of a ghost image of the object. Here for the first time we present ghost network analyzer for obtaining frequency properties of a target. Interestingly, this novel technique proves insensitive to the distortion introduced by nonlinear devices, while conventional frequency-domain measurement modalities such as network analyzer can hardly work properly with distortion. The proposed technique provides a breakthrough method for distortion-free dynamic frequency response analysis.